Improving the management of acute asthma in children through an integrated care pathway: an implementation study protocol - Montejo, Marta; Paniagua, Natalia; Sanchez, Alvaro; Rueda-Etxebarria, Mikel; Pijoan, Jose I.; Saiz Hernando, Carlos; Martin, Vanesa; Vázquez Ronco, Miguel Angel; Santiago Burruchaga, Mikel; García Urabayen, Diego; Pérez Llarena, Garbiñe; Castelo, Susana; et al. (Frontiers in Pediatrics, 2025)
IntroductionThis study aims to evaluate the effectiveness and feasibility of the implementation of an Asthma Integrated Care Pathway (AICP) to improve care and reduce variability according to recommended clinical practice guidelines, for children presenting with acute asthma episodes in paediatric primary care, and hospital services including emergency departments.Methods and analysisA cluster quasi-experimental implementation trial with a matched control group will be launched in a regional healthcare service. All the paediatric healthcare professionals providing care in two health districts (HDs) will receive interventions over two 12-month periods during which components of the implementation strategy to favour adoption of the AICP will be deployed cumulatively. A selected set of professionals from the same levels of care in the other HDs (N = 11) will serve as the comparison group. The target population of the AICP is children between 2 and 14 years old presenting with an acute asthma episode during the study period. A mixed methods evaluation guided by the RE-AIM framework will assess the effectiveness of the AICP after 12, 24, and 36 months in a set of pre-specified care and implementation outcomes at the professional level. The perceived feasibility of the AICP and its implementation from the perspective of physicians and the experience and satisfaction of patients concerning the clinical care received will be assessed through discussion groups.DiscussionThis study performed in real-world settings will contribute in extending knowledge in asthma care pathways beyond emergency settings into primary care and across the healthcare continuum. In addition, its findings aim to guide health systems in reducing variability in care, increasing guideline adherence, and ultimately improving paediatric asthma outcomes across the system. Clinical trial registrationClinicalTrials.gov, identifier [NCT06437444].